Pooled CRISPRi screening of the cyanobacterium Synechocystis sp PCC 6803 for enhanced industrial phenotypes - Lun Yao (Nature Portfolio, 2020)
Developing cyanobacteria as CO2-neutral cell factories relies on the knowledge of the regulation mechanisms for growth and metabolism. Here, the authors develop an inducible CRISPRi gene repression library in Synechocystis sp. PCC 6803 and screens genes potentially affecting growth and L-lactate tolerance and production.